Celestial eaudiobook - Wildenstein, Olivia (Angels of Elysium, 2023)
A heavenly mix of heartache and triumph, CELESTIAL is so feathering perfect. - CASEY L. BOND, bestselling author of With Shield and Ink and Bone In ninety-two days, the feathered appendages that link me to the people I loathe finally come off. Dear, winglets, you will not be missed. Celeste has spent the last four years building a life outside of angelic guilds—parties, check—pursuing human ambitions instead of celestial ones—college, check—and shedding feathers across Parisian cobblestones and more recently New York sidewalks—speaking her mind, always check. She swore off angels, but the death of the woman who took her in the night Leigh died brings them soaring back into her life . . . and not just any angel but the most detestable one, the one complicit in Leigh's death—Seraph Asher. Although Celeste tells the archangel to feather off, the unreasonably pretty and obstinate man doesn't leave her alone. He returns and insists she complete her wings. When she asks him for one good reason to do so, he gives her an unbeatable one: what he did with Leigh's soul. Asher never meant to share his damning secret, but he knows it's the only way to save Celeste—the rebellious Fletching he can't get out of his head . . . or heart. * WARNING: contains graphic scenes. Recommended for 18+.